2015
DOI: 10.1002/esp.3719
|View full text |Cite
|
Sign up to set email alerts
|

High resolution mapping of supra‐glacial drainage pathways reveals link between micro‐channel drainage density, surface roughness and surface reflectance

Abstract: This paper reports on the use of a small unmanned aerial vehicle (sUAV) carrying a standard compact camera, to construct a high resolution orthomosaic (OM) and digital elevation model (DEM) over the lower reaches of the glacier Midtre Lovénbreen, Svalbard. Structure from Motion (SfM) techniques were used to build the OM and DEM, and together these reveal insights into the nature of supra‐glacial drainage. Major meandering supra‐glacial drainage pathways show clear dynamism, via meander cutoffs and abandoned ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(130 citation statements)
references
References 45 publications
3
127
0
Order By: Relevance
“…DEMs are increasingly available at high resolution for ice surfaces [4,16,18,20], and reproducible, accurate methods of extracting surface meltwater channels are necessary for quantifying their temporal and spatial characteristics. Flow routing has numerous advantages for delineating meltwater channels; however, previous research by Yang et al (2015) [34] on the use of flow routing over moderate-resolution ice surface DEMs found that (1) automated sink preservation thresholds missed over half of mapped moulins and resulted in significantly overestimated drainage network extent; (2) mapped channel networks could be replicated by flow routing with match rates in excess of 85% when a 600 m buffer was applied; (3) less than 40% of the FR drainage network did not match the mapped drainage network, leading to the conclusion that these channels were miscoded.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…DEMs are increasingly available at high resolution for ice surfaces [4,16,18,20], and reproducible, accurate methods of extracting surface meltwater channels are necessary for quantifying their temporal and spatial characteristics. Flow routing has numerous advantages for delineating meltwater channels; however, previous research by Yang et al (2015) [34] on the use of flow routing over moderate-resolution ice surface DEMs found that (1) automated sink preservation thresholds missed over half of mapped moulins and resulted in significantly overestimated drainage network extent; (2) mapped channel networks could be replicated by flow routing with match rates in excess of 85% when a 600 m buffer was applied; (3) less than 40% of the FR drainage network did not match the mapped drainage network, leading to the conclusion that these channels were miscoded.…”
Section: Discussionmentioning
confidence: 99%
“…Supraglacial meltwater channels are ubiquitous fluvial features in the ablation zones of glaciers and ice sheets (e.g., [1][2][3][4]). They are of intrinsic interest to researchers as unique fluvial systems as well as for the important roles they play in glacial hydrology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rippin et al (2015) shows that greater density of microscale channels is associated with rougher, darker ice. Since roughness is a key parameter in surface energy balance it likely influences hole morphology, which impacts cryoconite biogeochemistry (Cook et al, 2010) and reciprocally influences surface roughness.…”
Section: Biocryomorphologymentioning
confidence: 96%